Bilingual Spanish-English Intergenerational Groups' Experiences in Bilingual Exhibitions. (April 2015) - Yalowitz, Steven S.; Garibay, Cecilia; Renner, Nan; Plaza, Carlos
Abstract : The Bilingual Exhibits Research Initiative examined the extent to which Spanish-speaking groups (defined as intergenerational groups who speak Spanish most or all of the time at home) engage in and use Spanish–English bilingual interpretation in informal science education institutions. Thirty-two bilingual Spanish-speaking groups were observed and interviewed about their visit to a bilingual exhibition. Groups were observed to read and talk in both Spanish and English. Adults were more likely to use Spanish compared to children, who used English more often. The groups often engaged in code switching, going back and forth seamlessly between the two languages. The findings confirmed that access to content is an important affordance of including bilingual interpretation, since ability to read in English often varied in intergenerational Spanish-speaking groups. Further research is needed to expand on this exploratory study to determine how institutions can most effectively employ bilingual interpretation for Spanish-speaking visitor groups, given that the use of bilingual interpretation was more complex than originally envisioned.